Differences in immunological profile in atopic dermatitis patients with and without dupilumab therapy - Čelakovská, Jarmila; Čermáková, Eva; Boudková, Petra; Andýs, Ctirad; Krejsek, Jan (Immunological medicine, 2025)
Our aim is to determine the number of leukocytes, T lymphocytes and B lymphocytes and the expression of activation markers CD200 and CD23 on B lymphocytes in atopic dermatitis (AD) patients (treated and not treated with dupilumab) during the pollen season. We examined 29 patients not treated with dupilumab, 24 patients treated with dupilumab and 40 healthy subjects as a control group. The count of T and B lymphocytes and their subsets were assessed by flow cytometry. The non-parametric Kruskal-Wallis one-factor analysis of variance with post hoc by Dunn's test with Bonferroni's modification was used for statistical processing. Although there was a significant improvement in skin findings in patients treated with dupilumab, the changes in immunological profile show a persistent altered immune response characterized by dysregulation and overactivation of B lymphocytes. Dupilumab therapy leads to normalization of relative T regulatory lymphocytes and total memory B lymphocytes and to decreased count of absolute CD8+ T lymphocytes. Why carry out this study?Studies investigating the immunological profile of atopic dermatitis (AD) patients during the pollen season are rare. There are no studies investigating the count of B lymphocytes (CD5+, CD22+ and CD73+ B lymphocytes) and the expression of activation markers CD23 and CD200 on B lymphocytes and on their subsets during pollen season in AD patients treated and non-treated with dupilumab therapy.What was learned from the study?In atopic dermatitis (AD) patients with and without dupilumab therapy, we confirmed the significantly higher count of absolute neutrophils, absolute monocytes, absolute eosinophils, absolute basophils, non-switched B lymphocytes, transitional B lymphocytes, CD23 memory, naive, non-switched, switched and total CD23 B lymphocytes, the relative count of CD200 memory and CD200 switched B lymphocytes.In dupilumab treated patients, we confirmed the significantly higher count of relative eosinophils, relative CD16+ eosinophils, relative CD200 non-switched B lymphocytes and lower count of absolute CD8+ T lymphocytes. Further studies should focus on investigating the effect of dupilumab on CD8+ T lymphocytes and their subpopulations.In patients without dupilumab therapy, we confirmed the significantly higher count of relative neutrophils, relative T regulatory lymphocytes and total memory B lymphocytes.The changes in the count of CD5+, CD22+ and CD73+ B lymphocytes were not observed during pollen season in both groups of AD patients.
Keywords: Antigens, CD; Dermatitis, Atopic; CD antigeny; Humans; lidé středního věku; Female; mladý dospělý; dospělí; lidé; humanizované monoklonální protilátky; B-lymfocyty; receptory IgE; Adult; Antibodies, Monoclonal, Humanized; ženské pohlaví; Male; Middle Aged; Pollen; Receptors, IgE; B-Lymphocytes; atopická dermatitida; Young Adult; pyl; mužské pohlaví